Monetary and Financial Policy in the Euro Area An Introduction - Fandl, Maximilian (Springer Texts in Business and Economics,, 2018)
This textbook provides a comprehensive overview of monetary policy, banking supervision and financial stability in the euro area. The author uses his professional experience in central banking to provide a thorough understanding of European economics and to explore how the monetary and financial system functions. The book takes into account the profound changes that resulted from crisis developments in recent years, such as the implementation of quantitative easing or the establishment of the Single Supervisory Mechanism (SSM). The author also invites readers to develop their thoughts on alternative policies to shape the monetary and financial system of the future. The textbook is tailor-made for intermediate courses in economics but will also appeal to those preparing a career in central banking or financial regulation.